Safety Behaviour Assessement Among Worker at Ink Manufacturing Industry - Wan Sofwa Najha Wan Samsudin; A. Kadir, Zuritah; Mohd Mustazza Nazri (Progress in Engineering Application and Technology, 2024)
Manufacturing industry is recorded as the highest accident and fatality case in Malaysia. Most of the accident cause based unsafe behaviour among workers. The aim of this study was to assess the state of safety in ink manufacturing industry. In order to achieve the first objective, the researcher using survey questionnaire the data were analysed by using Statistical Package for the Social Science (SPSS) software. The survey was distributed to 59 staff of plant 1 selected area. For the second objective of study are collected by checklist observation and percent safe was made to analyse the data.  Based on the result, it was found that safety implementation is high meanwhile the safety behaviour of employees are range 40% to 50% of percent safe. It shows that the safety behaviour among workers in this manufacturing company was moderate.